Design and analyses of reconfigurable dumbbell-shaped and modified H-Shaped DGSs in millimeter wave band - Shairi, Noor Azwan; Mohd Yasin, Fatin Nadiah; Othman, Adib; Zakaria, Zahriladha; Mohd Ibrahim, Imran; A Majid, Huda; Jamaluddin, Mohd Haizal; Ibrahim, Ayman Mohammed (Wydawnictwo SIGMA-NOT, 2023)
The design and analyses of reconfigurable dumbbell-shaped and modified H-shaped Defected Ground Structures (DGS) in the millimeter wave band (26/28 GHz band) are presented in this paper. The proposed DGSs were designed to be a reconfigurable between bandstop and allpass responses that would be used for 5G interference mitigation and as well as in RF switch design. In the design process, a mathematical model was developed for the analysis of reconfigurable capability between these two responses. Then, based on the E and H field concentration in the electromagnetic (EM) simulation, a suitable location of a PIN diode for the electronically controlled between bandstop and allpass was physically identify on the proposed reconfigurable DGS. Finally, a preliminary verification with an ideal PIN diode (open and short circuited) on the fabricated design was validated with the simulation results. Results showed that the proposed reconfigurable DGS can be changed between bandstop and allpass. The attenuation of the bandstop was more than -20 dB and the insertion loss of the allpass was lower than -3 dB in the 26/28 GHz band.